1995
DOI: 10.1177/026835559501000402
|View full text |Cite
|
Sign up to set email alerts
|

Venous Reflux at the Sapheno-Femoral Junction

Abstract: Objective,: To clarify reflux patterns in the saphenofemoral junction in legs with varicose veins that display incompetence in the proximal long saphenous vein on duplex scan examination. Padenls and method: One hundred consecutive extremities were selected for ultrasound studies. Venous reflux was examined in the common femoral vein and long saphenous vein at five selected levels in the vicinity of the sapheno-femoral junction. Results: Duplex ultrasound examination confirmed that in 44 extremities reflux was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
1
15
1
1
Order By: Relevance
“…Moreover, the finding of a competent terminal valve was more common than usually thought: 281 (63·1 per cent) of 445 legs in the present study. Cappelli and co‐workers26, 27 reported terminal valve competence in 45 per cent of legs, whereas Somjen and colleagues34 and Van Bemmelen et al 35 recorded 56 per cent and 78 per cent respectively. Thus, in current practice, application of the proposed duplex protocol could identify a group of about half of the patients with varicose veins who could benefit from a minimally invasive surgical approach, without the need for saphenofemoral ligation.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the finding of a competent terminal valve was more common than usually thought: 281 (63·1 per cent) of 445 legs in the present study. Cappelli and co‐workers26, 27 reported terminal valve competence in 45 per cent of legs, whereas Somjen and colleagues34 and Van Bemmelen et al 35 recorded 56 per cent and 78 per cent respectively. Thus, in current practice, application of the proposed duplex protocol could identify a group of about half of the patients with varicose veins who could benefit from a minimally invasive surgical approach, without the need for saphenofemoral ligation.…”
Section: Discussionmentioning
confidence: 98%
“…24 The SFJ is a complex anatomical and functional unit, and few studies on prevalence of reflux at this level take this peculiarity into account. Thus, although it is common to read the distinction between SFJ reflux and competent SFJ with reflux from proximal veins in the studies that make reference to the strategy known as Cure Conservatrice et Hemodynamique de l=Insuffisance Veineuse en Ambulatoire (CHIVA), 20 very few studies specify its differentiation and frequency, 25,26 and only an occasional study would exceptionally mention the possibility of the AAGSV being the only origin of the VVs. 22 Jiang et al 27 found an incidence of non-saphenofemoral venous reflux in 6.1% of cases of primary VVs.…”
Section: Discussionmentioning
confidence: 99%
“…[71][72][73] Furthermore, also postoperative analysis changed its perspective as clinical aspects could be verified by Duplex revealing a much higher recurrence rate. 74 In particular, it became clear that GSV reflux is not always associated to SFJ incompetence; 75 79 ). In this instance junction dissection and high ligation is useless 80 and even harmful, the source of reflux coming from a perforator or tributaries.…”
Section: The Duplex Adventmentioning
confidence: 99%